Editorial N. 59 september 2024 - Equipo Editorial (2024)
The team at Revista San Gregorio is pleased to welcome you to our 59th edition, a milestone that demonstrates our ongoing dedication to consistency and excellence in scientific publishing. We take pride in maintaining our presence in renowned databases such as Clarivate Analytics (Emerging Sources Citation Index), Latindex (Catalog 2.0), SciELO-Ecuador, DOAJ, REDIB, and Dialnet, among others, ensuring the visibility and impact of our scientific contributions.